1996
DOI: 10.1007/bf00023855
|View full text |Cite
|
Sign up to set email alerts
|

Screening RAPD primers for molecular taxonomy and cultivar fingerprinting in the genus Actinidia

Abstract: Eighty ten-base long arbitrary primers were tested for PCR-based DNA amplification of three species of the genus Actinidia (A . deliciosa the kiwifruit, A . chinensis, and A . kolomikta), with the aim of screening species-specific and genotype-specific markers .Of the 80 primers tested, 30 gave an average of 3 .5 bands which were monomorphic within one or two species and absent in the remaining one(s), thus resulting in useful markers for taxonomic and phylogenetic purposes . None of the primers tested produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
1
25
0
2
Order By: Relevance
“…It produces a large number of easily generated markers without the need of previous knowledge of the genome. The success of RAPD markers for taxonomic and evolutionary studies has been observed in several plant species such as Stylosanthes (Kazan et al, 1993), Malus (Dunemann et al, 1994), Actinidia (Cipriani et al, 1996), Pisum (Hoey et al, 1996), Vigna (Santala et al, 1998) and Ananas (Ruas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It produces a large number of easily generated markers without the need of previous knowledge of the genome. The success of RAPD markers for taxonomic and evolutionary studies has been observed in several plant species such as Stylosanthes (Kazan et al, 1993), Malus (Dunemann et al, 1994), Actinidia (Cipriani et al, 1996), Pisum (Hoey et al, 1996), Vigna (Santala et al, 1998) and Ananas (Ruas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Of these markers, RAPD markers (Wiliams et al, 1990) that result from the PCR amplification of genomic DNA fragments using short oligonucleotides (usually 10-mers) of arbitrary sequence as primers have been widely used for diversity analyses as they are simple to use, cost effective and amplify multiple DNA loci through PCR (Wiliams et al, 1990;Abkenar and Isshiki, 2003;Baig et al, 2009). Other advantages of RAPD include requirement of very small amounts of genomic DNA, elimination of blotting and radio-active detection steps (Cipriani et al, 1996). For these reasons many fruit tree crops have been successfully fingerprinted using RAPD markers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…RAPD assay has the advantage of being easy to use, requiring very small amount of genomic DNA without the need for blotting and radioactive detection (Cipriani et al, 1996;Atienzar et al, 2000), and are moderately reproducible. In this research, an attempt has been made to fingerprint and study their genetic relationship using RAPD markers, which could be very helpful for germplasm management, crop improvement and plant varietals rights.…”
Section: Introductionmentioning
confidence: 99%